PSYCHOLOGICAL AND BEHAVIOURAL IMPACTS OF ONLINE EXPLICIT CONTENT ON AE-FUNAI STUDENTS - Nwoga, Chibuzor Cosmas; Ibe, Kingsley Chinemerem; Nwankiti, Chukwuemeka Ononuju; Chime-Nganya, Chioma Rose; Obin, Ogban Obin; Ngwu, Ogonnaya Lynda (African Journal of Social and Behavioural Sciences, 2025)
The study examined the effects of exposure to online explicit content among undergraduate students in Nigeria, using students of AE-FUNAI as a proxy. The objectives were to: assess the perception and attitudes of AE-FUNAI students towards online explicit contents; examine the psychological effects of exposure to online explicit contents on the behaviour and well-being of AE-FUNAI students; and to investigate the extent of peer influence and social media in shaping the consumption of online explicit contents on AE-FUNAI students. The study, which adopted a survey research design, was anchored on Albert Bandura’s social learning theory. The sample size was 389, obtained through the Taro Yamane method. Three hypotheses were raised and tested using the Chi-square goodness of fit method. Data was analysed using the percentage and 4-point Likert scale with the decision point of 2.5. The study found a significant correlation between AE-FUNAI students’ perceptions of online explicit content and their sexual behaviours; exposure to explicit content has a significant impact on the behaviour and well-being of AEFUNAI students; and peer influence and social media have significantly aided in shaping the consumption of online explicit content by AE-FUNAI students. The study recommended the implementation of comprehensive sexuality education programs in secondary schools and universities, the establishment of counselling centres on university campuses that specifically address issues related to pornography addiction, and the promotion of media literacy to curb underage access to explicit sites.